A Review on Phytochemistry and Pharmacology of Macaranga peltata - Megha M; Kavana D K; Rithin K; Ramdas Bhat (International Journal of Tropical Medicines, 2024)
Macaranga peltata, categorized within the Euphorbiaceae family, represents a prevalent pioneer arboreal species across Southeast Asia, specifically in regions such as India and Sri Lanka. This review scrutinizes the phytochemical properties and pharmacological profiles of Macaranga peltata, underscoring both its historical medicinal applications and prospective therapeutic roles. The plant exhibits a rich composition of secondary metabolites, encompassing flavonoids, stilbenes, tannins, and terpenes, with the majority of these compounds being extracted from its foliar structures. Pharmacological investigations have substantiated a myriad of biological activities attributed to extracts of Macaranga peltata, which include antimicrobial, antioxidant, anti-inflammatory, anticancer, antifungal, wound healing, and hepatoprotective effects. Traditional applications of Macaranga peltata within indigenous medicinal frameworks involve the treatment of febrile conditions, dermatological ailments, gastrointestinal disorders, and lacerations. The multifaceted nature of the plant is further exemplified by its utilization as green manure and in the manufacturing of matchboxes and pencils. This review aggregates pertinent information regarding the distribution, morphological characteristics, phytochemical composition, and pharmacological efficacy of Macaranga peltata, thereby offering a thorough examination of its potential as a reservoir of bioactive compounds for therapeutic endeavors. Additional research is essential to isolate bioactive constituents and clarify their mechanisms of action, particularly in the context of oncological treatment.
Keywords: Bioactive compounds; Macaranga peltata; pharmacology; phytochemistry; traditional medicine